The Practice of Londo Iha in Kandai Ii Village, Balibunga Neighborhood: A Study on Marriage That Is Contrary to Islamic Law - Mentari, Dwi Radha Putri (STAINI Press, 2026)
Elopement Marriage (Londo Iha) in the Customs of the Mbojo and Dompu Tribes, West Nusa Tenggara, is a form of marriage that is not based on parental approval but rather on the will of both parties involved. The proposal and/or consent for the marriage between the two parties occur after the elopement, because the elopement happens due to refusal or unwillingness to propose, rejection of the proposal, disapproval from the parents, feeling disadvantaged, or having certain intentions. The research problems in this study are: First, what factors underlie the practice of londo iha marriage in Kandai Dua Village, Balibunga Environment? Second, what is the Islamic legal perspective on the practice of londo iha marriage? The research approach used in this journal is a literature study.The research results show that: Motives for Elopement Marriage: The majority of couples engage in elopement due to family rejection, social status differences, or strict customary procedures. Some also do it out of strong love and the desire to marry immediately. Social Impact: Elopement causes tension within families and communities but also opens up space for renegotiating customary norms. In some cases, couples who elope eventually receive recognition and acceptance from their families. Community Views: Traditional societies still consider elopement controversial and contrary to customary rules, but there is a growing tendency to accept social change.The discussion indicates that elopement is a form of social resistance as well as an adaptation to changing values and social structures.